2023
DOI: 10.3126/ije.v12i1.52441
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Tolerance of Bacterial Isolates from Solid Waste Dumping Sites in Abuja, Nigeria

Abstract: Bacteria have special bio-mechanism to resist toxic heavy metals. This study investigated heavy metal tolerance potentials of bacterial isolates from solid waste dumping sites (Abaji, Bwari, Gosa, Gwagwalada, Kuje, and Kwali) in Abuja, Nigeria. Soil samples were randomly collected from each location using soil augers at depths of 0 – 15, 15 – 35 and 35 – 45 cm. They were analyzed bacteriologically using cultural/biochemical techniques and chemically by exposing the isolates to graded concentrations (50 - 400 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Ibrahim et al (2020), confirmed the detection of Cd, Cu and Pb in soils of 10 solid waste dumpsites in Potiskum, Yobe State Nigeria which were above the WHO set limits. In addition, Ojiego et al (2022) reported the heavy metal pollution of Ni, Cr, Pb, Cd and Zn from 24 soils sampled from Kuje and Kwali solid waste dumpsites, Abuja, Nigeria. Li et al (2019), stated that about 5 million soil sites worldwide are heavy metal polluted exceeding regulatory levels.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Ibrahim et al (2020), confirmed the detection of Cd, Cu and Pb in soils of 10 solid waste dumpsites in Potiskum, Yobe State Nigeria which were above the WHO set limits. In addition, Ojiego et al (2022) reported the heavy metal pollution of Ni, Cr, Pb, Cd and Zn from 24 soils sampled from Kuje and Kwali solid waste dumpsites, Abuja, Nigeria. Li et al (2019), stated that about 5 million soil sites worldwide are heavy metal polluted exceeding regulatory levels.…”
Section: Introductionmentioning
confidence: 99%